Ombudsmen in the United Kingdom - Yardley, Sir David (Journal of Malaysian and Comparative Law, 2019)
Government action is generally accountable in law in the United Kingdom, usually through court proceedings. Yet there have always been some areas of administrative power or executive discretion which have remained immune from the possibility of judicial review. A decision made by an administrative officer which is within his lawful jurisdiction, and which is made neither in breach of natural justice nor in error of law may well therefore be valid, and of course technically reasonable, but nevertheless harsh, or delayed, or inadequately explained.